Analysis Of Transportation System Development In Transit-Oriented Development (TOD) Area Of Rawa Buntu, South Tangerang - Mohamad Ivan Aji Saputro; Andyka Kusuma; Vian Marantha Haryanto (Eduvest - Journal of Universal Studies, 2024)
This study examines Transit Oriented Development (TOD) in South Tangerang City, focusing on the Rawa Buntu TOD area. TOD aims to integrate public transportation modes with non-motorized networks, fostering sustainable mobility and reducing dependence on private vehicles. The research highlights the policy framework and infrastructural developments supporting TOD in South Tangerang, such as Regional Regulation No. 9 of 2019 and Mayor Regulation No. 118 of 2022. Employing mixed methods, including surveys, field observations, literature reviews, and spatial analysis, the study assesses the transportation system and infrastructure conditions. Results show that most roads in South Tangerang are in good condition, with significant movement patterns between key districts. Rawa Buntu Station, a strategic transit node, demonstrates robust integration with various transportation modes, serving approximately 11,000 passengers daily. The study concludes that Rawa Buntu TOD area boasts comprehensive transportation infrastructure and efficient services, enhancing urban connectivity and sustainability.